ANALISIS DIMENSI MUTU PELAYANAN KESEHATAN TERHADAP KEPUASAN PASIEN DI UNIT RAWAT INAP DAN RAWAT JALAN RSUD PASAR MINGGU - Ahid Nur Hidayati, (2023)
Types of services in a hospital that are mandatory in a hospital are inpatient and outpatient services. Good service can be assessed for its quality as seen from indicators of patient satisfaction. The purposes of theresearch was to determine the relationship between the dimensions of health service quality and the level of patient satisfaction in inpatient and outpatient care at RSUD Pasar Minggu based on IOM and WHO dimensions, which are: patient safety, patient-centered, timeliness, service effectiveness, service efficiency, and service accessibility. This study uses a quantitative method with a cross-sectional study approach. The minimum number of samples required is 106 respondents from each inpatient and outpatient unit. Data collection was carried out in December 2022 by distributing questionnaires. The data analysis performed was univariate and bivariate using the chi-square method with a 95% CI. The results show that in inpatient and outpatient units there is a relationship with the level of patient satisfaction, which are service effectiveness, service efficiency, accessibility of patient-centered services, patient safety, and timeliness. While timeliness in the outpatient unit is not related. RSUD Pasar Minggu must be able to maintain and improve health services based on the quality dimensions of health services by providing fast and responsive services.